Illicit antiquities and international litigationñthe Turkish experience - Blake, Janet
In March, we discussed the founding of the Illicit Antiquities Research Centre (IARC) at the McDonald Institute in Cambridge (ANTIQUITY 72: 4Ð5). Here we publish a contribution towards the debate on the theft of antiquities from Turkey and their acquisition by museums in the USA. Turkey has long had an active policy in fighting cases for restitution of its heritage, and Janet Blake describes their success.